Wpływ opodatkowania na inwestycje w warunkach rosnącej konkurencji podatkowej - Kluzek, Marta (Influence of Taxation on Investment Under Conditions of Growing Tax Competition, 2006)
This paper presents the essence of tax competition and the impact of international tax rules on foreign direct investment. Generally speaking "tax competition" is referred to as the lowering of the tax burden in order to improve a country's economy and welfare by increasing the competitiveness of domestic business and/or attracting foreign investment. Economic theory has shown that tax competition may also cause a number of harmful economic effects. The number of countries worldwide offering some type of tax incentives for attracting especially foreign direct investment is increasing. Tax competition occurs through an array of different tax incentives relating to the corporate tax rate, the taxable base, or the final tax due in a certain country. The evidence, much of it recent, indicates that taxation significantly influences allocation of factors and products around the world.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 316-325